2018
DOI: 10.1148/radiol.2017162853
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion and Quantitative Non-Gaussian Diffusion MR Imaging: Evaluation of the Diagnostic and Prognostic Value of Several Markers of Malignant and Benign Breast Lesions

Abstract: Purpose To investigate the performance of integrated approaches that combined intravoxel incoherent motion (IVIM) and non-Gaussian diffusion parameters compared with the Breast Imaging and Reporting Data System (BI-RADS) to establish multiparameter thresholds scores or probabilities by using Bayesian analysis to distinguish malignant from benign breast lesions and their correlation with molecular prognostic factors. Materials and Methods Between May 2013 and March 2015, 411 patients were prospectively enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
88
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 33 publications
8
88
1
Order By: Relevance
“…Although our measurements were similar to those of most studies investigating IVIM parameters, some recent studies have provided histogram analysis, which could show less fitting artifacts from the parametric map. Second, the range of f value (9.82–48.56%) was relatively high as compared to those (0–46.74%) from the literature . Those high values likely reflect residual tissue diffusion, which can be attributed to the heterogeneity of the tumors.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Although our measurements were similar to those of most studies investigating IVIM parameters, some recent studies have provided histogram analysis, which could show less fitting artifacts from the parametric map. Second, the range of f value (9.82–48.56%) was relatively high as compared to those (0–46.74%) from the literature . Those high values likely reflect residual tissue diffusion, which can be attributed to the heterogeneity of the tumors.…”
Section: Discussionmentioning
confidence: 74%
“…Second, the range of f value (9.82-48.56%) was relatively high as compared to those (0-46.74%) from the literature. [5][6][7][8][9][10][11]31 Those high values likely reflect residual tissue diffusion, which can be attributed to the heterogeneity of the tumors. However, according to a recent study using histogram analysis, 6 the maximum f value of invasive breast cancers was reported as 46.74%, which was similar to our study result and we used the median value rather than the mean value in our statistical analysis to avoid average trap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of quality assessment for risk of bias and concerns regarding applicability of included studies. Quality assessment of diagnostic accuracy studies (QUADAS-2) scores for each category are expressed by percentages of studies that have a low, high, or unclear risk of bias.IVIM parameters and Iima et al(91) reported a combination of f, ADC, and diffusion kurtosis coefficient K.Jiang et al (27) also reported a combination of fractional anisotropy and the maximal anisotropy index.…”
mentioning
confidence: 95%